PENGARUH TECHNOLOGY ACCEPTANCE MODEL DAN PERCEIVED BENEFITS TERHADAP MINAT PENGGUNAAN APLIKASI SHOPEE FOOD PADA MASYARAKAT SURABAYA - Richard Wangsadinata; Clarissa Nathania Geraldine; Adriana Aprilia (Institute of Research and Community Outreach - Petra Christian University, 2021)
This research is conducted to examine the influence of Technology Acceptance Model (Perceived Usefulness, Perceived Ease of Use, and Trust) and Perceived Benefits (Price Saving Benefits and Time Saving Benefits) toward Surabaya consumers’ intention to use Shopee Food application. The questionnaire is distributed to 150 respondents that lived in Surabaya and used an Online Food Delivery application. The type of research is quantitative casual research and using multiple linear regression analysis. The result shows that Perceived Usefulness and Time Saving Benefits have a positive and significant effect on Surabaya consumers' intention to use Shopee Food application. Meanwhile, Perceived Ease of Use, Trust, and Price Saving Benefits have insignificant effect on Surabaya consumers’ intention to use Shopee Food application. Abstrak Penelitian ini dilakukan untuk mengetahui pengaruh Technology Acceptance Model (Perceived Usefulness, Perceived Ease of Use, dan Trust) dan Perceived Benefits (Price Saving Benefits dan Time Saving Benefits) terhadap minat penggunaan aplikasi Shopee Food pada masyarakat Surabaya. Kuesioner penelitian ini dibagikan kepada 150 responden yang berdomisili di Surabaya dan sudah pernah menggunakan aplikasi Online Food Delivery. Jenis penelitian ini adalah kausal kuantitatif dengan metode analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa Perceived Usefulness dan Time Saving Benefits berpengaruh positif dan signifikan terhadap minat penggunaan aplikasi Shopee Food pada masyarakat Surabaya. Sementara itu, Perceived Ease of Use, Trust, dan Price Saving Benefits berpengaruh namun tidak signifikan terhadap minat penggunaan aplikasi Shopee Food pada masyarakat Surabaya.